Morphology and development of the eodiscoid trilobite Tsunyidiscus yanjiazhaiensis from the Cambrian (Stage 3, Series 2) of South China. (2nd January 2016) - Dai, Tao; Zhang, Xingliang; Peng, Shanchi
Abstract : The post-protaspid ontogenetic series of the eodiscinid trilobite Tsunyidiscus yanjiazhaiensis S. Zhang et al . in Yin & Li, 1978 is described, on the basis of crack-out specimens including numerous articulated specimens and a large number of disarticulated sclerites from the lower Cambrian (Stage 3, Series 2) Shuijingtuo Formation, Zhenba County, Shaanxi Province, South China. In addition, hundreds of phosphatized sclerites assigned to this species were obtained by dilute acetic acid dissolution of thin-bedded limestones from the same horizon. These sclerites exhibit considerable morphological detail and even some delicate structures, such as the axial pores and marginal spines on the pygidium and the bacculae that can be retained from the protaspid to the holaspid period. Ontogenetic study of T. yanjiazhaiensis provides new evidence to support and reconfirm the unique developmental pattern shared by early Cambrian eodiscoid trilobites, i.e. the processes of liberation of the thoracic segment and segment insertion into the pygidium are separate from one another. This represents a highly unusual growth pattern among the Trilobita and offers fresh insights into segmentation during postembryonic development of eodiscinid trilobites.